PENGGUNAAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN APRESIASI MUSIK DI KELAS IX.2 SMP NEGERI 7 PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the reasons teachers choose audio-visual media and its use in teaching music appreciation in class IX.2 at SMP Negeri 7 Padang. The study uses a qualitative research method with a descriptive approach. The research object is the use of audio-visual media in music appreciation lessons. Data was obtained through observation, interviews, and documentation. The research informants consisted of the Music Arts teacher and two students from class IX.2 at SMP Negeri 7 Padang. Data was analysed through the stages of data reduction, data presentation, data classification, and drawing conclusions. The results showed that teachers choose audio-visual media because it can combine sound and visuals, helping convey music appreciation material more concretely. The use of audio-visual media is carried out in three stages, namely planning, implementation, and evaluation. In the planning stage, the teacher prepares a PPT, music performance videos, a laptop, an LCD projector, and speakers. During the implementation stage, the teacher uses the PPT to deliver the material and the music performance videos for appreciation, then the students observe, discuss, and work on worksheets. In the evaluation stage, the teacher reviews the use of media and devices used during the learning process. Thus, the use of audio-visual media in music appreciation lessons in class IX.2 at SMP Negeri 7 Padang has been carried out in a planned manner using various integrated media and learning devices.